Extraction of Galactomannan on the Coconut Meat, “Sapal”, and Function for Food - Rindengan Barlina (Puslitbang Perkebunan, 2015)
ABSTRACTGalactomannan is a polymer containing units mannopiranosa with βeta-(1-4) and unit galactopiranosa with bonding αlfa-(1-6). Galactomannan source that has been developed is of plant seeds Leguminoceae, the fenugreek (Trigonellafoenum graecum). The price of 250 mg extract of fenugreek yield 85% galactomannan reach to US 26.75 (Rp.250,000). Galactomannan compound also contained in the coconut meat. The more mature of coconuts fruit, galactomannan compounds will increase. Coconut pulp that has been processed into flour can be substituted on the processing of snacks so that the product has Glykemik index (GI) is low. Isolation galactomannan using 4% of furnace ash solution and coconut pulp 400 g obtained galactomannan isolates 134,4g. The use of coconut galactomannan isolates for 52 days in the rabbit (hypercholesterolemia), can prevent the increase in total cholesterol levels of 24 mg / dl, cholesterol- drugs only 16 mg /dl, preventing the increase in LDL of 15 mg /dl together with cholesterol- drugs, increase HDL 1 mg /dl, while the drug to increase HDL 2 mg /dl, and prevent the increase in triglycerides (TG) 18 mg /dl. By looking at the benefits galactomannan in the food industry, health, environmental and economic value, this potential needs to develope.Keywords: Coconut, sapal, galactomannan, isolation, food, health Ekstrak Galaktomanan pada Daging Buah Kelapa dan Ampasnya serta Manfaatnya untuk Pangan RINGKASANGalaktomanan adalah polimer yang mengandung unit mannopiranosa dengan ikatan βeta– (1– 4) dan unit galaktopiranosa dengan ikatan αlfa – (1– 6). Sumber galaktomanan yang telah dikembangkan adalah dari biji tanaman Leguminoceae, yaitu fenugreek (Trigonellafoenum graecum). Harga 250 mg ekstrak fenugreek berkadar 85% galaktomanan mencapai US 26,75 atau Rp.250.000.- Senyawa galaktomanan terkandung juga pada daging buah kelapa. Semakin matang buah kelapa berat galaktomanan akan meningkat dan terbukti pada ampas kelapa terkandung kadar galaktomanan yang tinggi. Galaktomanan memiliki banyak manfaat dalam industri pangan, kesehatan dan lingkungan hidup. Ampas kelapa yang telah diolah menjadi tepung dapat disubstitusi pada pengolahan makanan ringan sehingga produk memiliki Indeks Glykemik (IG) rendah. Isolasi galaktomanan menggunakan larutan isolat abu tungku 4% pada ampas kelapa 400 g diperoleh berat kering isolat galaktomanan 134,4g. Penggunaan isolat galaktomanan kelapa selama 52 hari pada kelinci percobaan (hiperkolesterol), dapat mencegah kenaikan kadar total kolesterol 24 mg/dl, obat penurun kolesterol hanya 16 mg/dl, mencegah kenaikan LDL 15 mg/dl sama dengan obat penurun kolesterol, meningkatkan HDL 1 mg/dl, sedangkan yang diberi obat meningkatkan HDL 2 mg/dl dan mencegah kenaikan trigliserida (TG) 18 mg/dl. Dengan melihat manfaat galaktomanan dalam industri pangan, kesehatan, lingkungan hidup dan nilai ekonomi yang cukup baik, maka potensi ini perlu dikembangkan.Kata kunci: Kelapa, ampas, galaktomanan, isolasi, pangan, kesehatan